Cell‐Traction‐Triggered On‐Demand Electrical Stimulation for Neuron‐Like Differentiation. Issue 51 (15th October 2021) - Liu, Zhirong; Cai, Mingjun; Zhang, Xiaodi; Yu, Xin; Wang, Shu; Wan, Xingyi; Wang, Zhong Lin; Li, Linlin
Abstract: Electromechanical interaction of cells and extracellular matrix are ubiquitous in biological systems. Understanding the fundamentals of this interaction and feedback is critical to design next‐generation electroactive tissue engineering scaffold. Herein, based on elaborately modulating the dynamic mechanical forces in cell microenvironment, the design of a smart piezoelectric scaffold with suitable stiffness analogous to that of collagen for on‐demand electrical stimulation is reported. Specifically, it generated a piezoelectric potential, namely a piezopotential, to stimulate stem cell differentiation with cell traction as a loop feedback signal, thereby avoiding the unfavorable effect of early electrical stimulation on cell spreading and adhesion. This is the first time to adapt to the dynamic microenvironment of cells and meet the electrical stimulation of cells in different states by a constant scaffold, diminishing the cumbersomeness of inducing material transformation or trigging by an external stimulus. This in situ on‐demand electrical stimulation based on cell‐traction‐mediated piezopotential paves the way for smart scaffolds design and future bioelectronic therapies. Abstract : An innovative loop feedback strategy between cells and biominic biomaterials is proposed for cell fate modulation. A piezoelectric fibrous network with mechanical stiffness similar to that of collagen can be trigged by cell traction for on‐demand electrical stimulation to promote neuron‐like differentiation. This in situ on‐demand electrical stimulation paves the way for smart scaffold design and future bioelectronic therapies.